HUBUNGAN ADVERSITY QUOTIENT DENGAN PROKRASTINASI AKADEMIK MAHASISWA PROGRAM STUDI PG PAUD FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS RIAU ANGKATAN 2014 - ', MHD. Sanusi; ', Zulkifli N; Risma, Devi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstrack: The aim of this research is to know whether there is any correlation between students’ adversity quotient and academic procrastination in education program of Teacher Education Courses for Early Childhood Education and Faculty of Teacher Training and Education at University of Riau year 2014. The population of this research is the students of Teacher Education Courses for Early Childhood Education in Faculty of Teacher Training at University of Riau year 2014 that consists of 83 students, the samples of this research are 63 students. Method of this research is quantitative correlation to know the correation between independent variable and dependent variable. The technique of collecting data used quistioner in Likert scale form. The technique of analyzing data used scale test and statistic analitical by using SPSS program for Windows Ver.17. Based on the hypothesis there is any significant negative correlation between sudents’ adversity quotient and academic procrastination in Teacher Education Courses for Early Childhood Education Faculty of Teacher Training and Education at University of Riau year 2014. It could be seen from the result of correlation cooficient that rxy = -0,324 and significant level is 0,010 < 0,05. The correlation between students’ adversity quotient and academic procrastination is in the medium level which is the KP = r² x 100% = 10,50%, it means that adversity quotient affect the academic procrastination as much as 10,50%.Key Words: Adversity Quotient, Academic Procrastination